Analisis Perbandingan Hidrograf Satuan Sintetik Gama I dan SCS (HEC-HMS) dengan Hidrograf Satuan Terukur di Sungai Way Besai - Sembiring, Fadhel Dzaki; Kusumastuti, Dyah Indriana; Winarno, Dwi Joko (Universitas Lampung, 2019)
The Way Besai River is located in Sumber Jaya District, West Lampung Regency. River discharge is an indicator of watershed function in transforming rain into stream flow. River discharge is generally presented by hydrograph. There are two methods to derive unit hydrograph, i. e. Measured Unit Hydrograph method (HST) and Synthetic Unit Hydrograph method (HSS). Synthetic Unit Hydrograph is used if the watershed does not have sufficient hydrometry data for calculating flood discharge. The purpose of this study is to analyze Synthetic Unit Hydrograph Gama I, Synthetic Unit Hydrograph SCS (HEC-HMS), and measured unit hydrograph for Way Besai River. The method used in this study includes Synthetic Unit Hydrograph Gama I, Synthetic Unit Hydrograph SCS (HEC-HMS), and Measured Unit Hydrograph. The results of this study show that Unit Hydrograph derived from Synthetic Unit Hydrograph SCS (HEC-HMS) is better than the result derived from Synthetic Unit Hydrograph Gama I based on peak discharge, peak time, base time and base flow values. Keywords: Watershed, Discharge, Synthetic Unit Hydrograph, Measured Hydrograph Unit, SCS (HEC-HMS), Gama I.